Euro Area monetary policy and financial stress regimes: a threshold var approach - Martins, Daniela Soares (2020)
We investigate how the state of financial conditions affects the transmission of monetary policy to the euro area macroeconomy. Our main goal is to analyze the responses of output growth and inflation to monetary policy shocks during periods of low and high financial stress. Results from a Threshold Vector Autoregression model show that monetary policy is of negligible importance to the real economy during normal times. However, an effective tool to ease the state of financial conditions when the economy is already facing strains. Empirical evidence also suggests that in the short-run monetary policy cannot significantly influence the inflation rate.